An Experimental Study: Cartoon Videos as Media Instruction on Students Speaking Ability - s siswandi; firman rizaldi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
The main focus of this research is to investigate whether there was a significant difference in the speaking ability between the tenth grade students of SMA N 1 Kampar Timur. This research was classified as a quasi-experimental study. It involved 65 students of two groups, Class X MIPA 5 as the experimental group and Class X MIPA 6 as the control group. The experimental group was taught by using cartoon videos, whereas the control group was taught by using the textbook-based technique. The data were obtained by using a pre-test and a post-test. The pre-test was given to both groups before the treatment and the post-test was given after the treatment. The data of the pre-test and post-test of both groups were analyzed by using descriptive and inferential statistics. The data were calculated by using a computer program, SPSS 25 for Windows. After the data were tested and found to be homogeneous and normal, the hypothesis was tested using the Kolmogrov-Smirnov test. The results of the research show that there was a significant difference in the speaking ability between the students who were taught by using cartoon video and those who were taught by using the textbook-based technique. The significance value calculated 0.019 is bigger than 0.05 (sig value=0.109>0.05). Therefore, the hypothesis of this study is rejected. It means that there is no significant difference on students speaking ability who are taught by cartoon video as instructional media at the eleventh grade of senior high school 1 Kampar Timur.